Pharmacognostical Evaluation, Growth Inhibitory and Antioxidant Activities of Chasmanthera dependens Hochst. - Salawu, Kayode Muritala; Balogun, Quadri Olayinka; Sulaiman, Hikmat Opeyemi; Ologe, Mary Funmi; Salawu, Oluwatoyosi Olatoun (HAYATI Journal of Biosciences, 2025)
The absence of pharmacognostic criteria and inadequate crude drug quality control yardsticks are the primary reasons for medicinal plant misidentification, therapeutic failure, and toxicity associated with herbal medicines. This study aims to identify the macroscopic and microscopic features, physicochemical properties, important chemical constituents, and antioxidant and growth inhibitory potential of Chasmanthera dependens, a species found in the rainforest of West Africa. A detailed pharmacognostic evaluation of C. dependens was carried out, including macroscopic and microscopic characterization, phytochemical screening, and physicochemical analysis. Antioxidant and growth-inhibitory bioassays were performed to assess its bioactivity. Chasmanthera dependens is characterized by a cylindrical, partly long, rough-surfaced twig with evergreen, cordate leaves. Its exudate is odorless but slightly sweet, with a bitter aftertaste. Microscopic analysis revealed covering trichomes on both adaxial and abaxial leaf surfaces, with an anomocytic type of stomata only on the abaxial surface. The chemical analysis showed the fruit is rich in phytoconstituents like alkaloids, tannins, and flavonoids, as well as important micronutrients such as zinc, copper, cadmium, magnesium, manganese, protein, lipids, and fiber. The extracts demonstrated significant antioxidant and growth-inhibitory effects. This study provides the first detailed pharmacognostic features of C. dependens, contributing valuable data for its identification, quality control, and potential medicinal applications.